U źródeł polskiej krytyki filmowej: Antoni Słonimski - Hendrykowski, Marek (Przestrzenie Teorii, 2007)
The subject of this study is an almost completely forgotten chapter of the early literary work of Antoni Słonimski, which is his precursory activity on the ground of Polish film criticism of the years 1922-1923 in the columns of the all-Polish daily Kurier Polski. He had his own column there titled "Kinematograph" (Cinematograph). His essays on the cinema were written in the form of light feuilletons. Referring to the current repertoire of Warsaw cinemas, A. Słonimski tried as much as he could to go beyond the current premieres. He interested in a wider perspective which allows to describe cinema as a phenomenon of contemporary culture.